Development of the Cook-EdTM Matrix to Guide Food and Cooking Skill Selection in Culinary Education Programs That Target Diet Quality and Health - Roberta C. Asher (Nutrients, 2022)
Culinary education programs are generally designed to improve participants’ food and cooking skills, with or without consideration to influencing diet quality or health. No published methods exist to guide food and cooking skills’ content priorities within culinary education programs that target improved diet quality and health. To address this gap, an international team of cooking and nutrition education experts developed the Cooking Education (Cook-EdTM) matrix. International food-based dietary guidelines were reviewed to determine common food groups. A six-section matrix was drafted including skill focus points for: (1) Kitchen safety, (2) Food safety, (3) General food skills, (4) Food group specific food skills, (5) General cooking skills, (6) Food group specific cooking skills. A modified e-Delphi method with three consultation rounds was used to reach consensus on the Cook-EdTM matrix structure, skill focus points included, and their order. The final Cook-EdTM matrix includes 117 skill focus points. The matrix guides program providers in selecting the most suitable skills to consider for their programs to improve dietary and health outcomes, while considering available resources, participant needs, and sustainable nutrition principles. Users can adapt the Cook-EdTM matrix to regional food-based dietary guidelines and food cultures.